Legal aspects of the procedure for determining the fee for water services under new Water Law (Ius Novum, 2019)
The authors of this article analyse legal aspects of the procedure connected with determining charges for water services regulated in the new Water Law Act. First of all, the authors indicate interpretational doubts related to a specific form of decision-making procedure and also related to appeal procedure. The authors interpret legal regulations connected with the specific form used by the legislator within this procedure, i.e. “information” through which the Polish Water Management Enterprise (Wody Polskie) notifies the obliged entities of the amount of charge for water services. What is more, the authors try to attribute formal and legal status to such form of decision-making. An issue related to applying provisions of the Administrative Procedure Code within aforementioned procedure is also considered in relation to passing on the administrative decision and also to the appeal procedure. Under the applied research method, the authors refer to the interpretation of legal provisions, views of representatives of the doctrine, and the Constitutional Tribunal and administrative courts’ case law.
Keywords: water law; water services; charges for water services; annual information; administrative procedure; administrative decision